Assessing panic disorder-specific competencies: evaluation of the Cognitive Therapy Competence Scale for panic disorder. Issue 2 (8th March 2021) - Liness, Sheena; Beale, Sarah; Clark, David M.; Salkovskis, Paul M.; Ehlers, Anke; Wild, Jennifer
Abstract: Background: Evidence-based treatment for panic disorder consists of disorder-specific cognitive behavioural therapy (CBT) protocols. However, most measures of CBT competence are generic and there is a clear need for disorder-specific assessment measures. Aims: To fill this gap, we evaluated the psychometric properties of the Cognitive Therapy Competence Scale (CTCP) for panic disorder. Method: CBT trainees ( n = 60) submitted audio recordings of CBT for panic disorder that were scored on a generic competence measure, the Cognitive Therapy Scale – Revised (CTS-R), and the CTCP by markers with experience in CBT practice and evaluation. Trainees also provided pre- to post-treatment clinical outcomes on disorder-specific patient report measures for cases corresponding to their therapy recordings. Results: The CTCP exhibited strong internal consistency (α = .79–.91) and inter-rater reliability (ICC = .70–.88). The measure demonstrated convergent validity with the CTS-R ( r = .40–.54), although investigation into competence classification indicated that the CTCP may be more sensitive at detecting competence for panic disorder-specific CBT skills. Notably, the CTCP demonstrated the first indication of a relationship between therapist competence and clinical outcome for panic disorder ( r = .29–.35); no relationship was found for the CTS-R. Conclusions: These findings provide initial support for the reliability and validity of the CTCP for assessing therapist competence in CBT for panic disorder and support the use of anxiety disorder-specific competence measures. Further investigation into the psychometric properties of the measure in other therapist cohorts and its relationship with clinical outcomes is recommended.